Stochastic Assessment of the Economic Impact of Streptococcus suis-Associated Disease in German, Dutch and Spanish Swine Farms - Neila-Ibáñez, Carlos; Casal, Jordi; Hennig-Pauka, Isabel; Stockhofe-Zurwieden, Norbert; Gottschalk, Marcelo; Migura-García, Lourdes; Pailler-García, Lola; Napp, Sebastián (Frontiers in Veterinary Science, 2021)
The economic assessment of animal diseases is essential for decision-making, including the allocation of resources for disease control. However, that assessment is usually hampered by the lack of reliable data on disease incidence, or treatment and control measures, and that is particularly true for swine production diseases, such as infections caused by Streptococcus suis. Therefore, we developed a method based on a questionnaire-based surveys of clinical swine veterinarians to obtain the input data combined with a stochastic model to calculate the costs caused by S. suis, which was implemented in three of the main swine producing countries in Europe: Germany, the Netherlands and Spain. S. suis-associated disease is endemic in those countries in all production phases, though nursery was the phase most severely impacted. In affected nursery units, between 3.3 and 4.0% of pigs had S. suis-associated disease and the mortalities ranged from 0.5 to 0.9%. In Germany, the average cost of S. suis for each pig produced in the country was 1.30 euros (90% CI: 0.53-2.28), in the Netherlands 0.96 euros (90% CI: 0.27-1.54), and in Spain 0.60 euros (90% CI: 0.29-0.96). In Germany, that cost was essentially influenced by the expenditure in early metaphylaxis in nursery and in autogenous vaccines in sows and nursery pigs; in the Netherlands, by expenditures on autogenous vaccines in sows and nursery pigs; and in Spain, by the expenditures in early metaphylaxis and to a lesser extent by the mortality in nursery pigs. Therefore, the differences in costs between countries can be explained to a great extent by the measures to control S. suis implemented in each country. In Spain and in Germany, use of antimicrobials, predominantly beta-lactams, is still crucial for the control of the disease.